IMPROVING FINANCIAL ANALYSIS IN MEDICAL INSTITUTIONS - Khasanov Khusinboy Xudayberganovich (Modern American Journals, 2025)
This article examines the main indicators used to assess the financial condition of medical institutions: financial condition, profitability, liquidity turnover indicators, solvency and financial reporting. Based on the conclusions obtained as a result of the analysis of the activities of medical institutions, conclusions and proposals for improving the financial analysis of medical institutions were developed.
Keywords: Medical institution, profitability, liquidity, solvency, financial analysis.